Kajian Model Kinetika Adsorpsi Metilen Biru Menggunakan Karbon Berbasis Ampas Kelapa (Cocos nucifera L.) - Etriyanto Arman; Muhamad Alvin Reagen; Sonya Nurizki Vikandari (LPPM Universitas Dharma Andalas, 2026)
Water pollution caused by synthetic dyes, particularly methylene blue, has become a significant environmental concern due to its persistence and potential toxicity to aquatic ecosystems. The utilization of coconut pulp (Cocos nucifera L.) waste as a precursor for adsorbent production represents a promising alternative because of its abundant availability, low cost, and high carbon content, which enable the production of an effective and environmentally friendly adsorbent. This study aimed to investigate the effect of contact time and the adsorption kinetics of methylene blue using carbon derived from coconut pulp waste. Batch adsorption experiments were conducted using 0.2 g of adsorbent in 20 mL of a 50ppm methylene blue solution. The adsorption kinetics were evaluated using the pseudo-first-order and pseudo-second-order kinetic models. FTIR characterization confirmed the presence of characteristic functional groups in the coconut pulp-derived carbon. The adsorption process exhibited increasing adsorption capacity and removal efficiency with increasing contact time until equilibrium was reached, with maximum values of 3.63 mg g⁻¹ and 72.78%, respectively. Kinetic analysis revealed that the adsorption process was better described by the pseudo-second-order model than by the pseudo-first-order model, as indicated by a higher coefficient of determination (R² = 0.9858) and an adsorption rate constant (k₂) of 1.04 × 10⁻¹ g mg⁻¹ min⁻¹. These findings demonstrate that carbon derived from coconut pulp waste has considerable potential as an effective, economical, and sustainable alternative adsorbent for the treatment of dye-containing wastewater.